New Ustazah: Hijrah & Transformation of Da'wa Authority among Celebrities in Indonesia - Umdatul Hasanah; Ilah Holilah; Sharifah Fadylawaty Binti Syed Abdullah (Jurnal Dakwah Risalah, 2025)
This study examines the phenomenon of celebrities who have undergone hijrah (spiritual migration) and subsequently taken on roles as religious preachers. The rise of celebrity ustazah significantly impacts the da'wa landscape, altering both the authority and perception of Islamic propagation. Many celebrities embracing hijrah not only undergo spiritual transformation but also contribute to a shift in the structural dynamics of religious outreach. Through these channels, celebrity ustazah emerge as influential religious figures, sometimes challenging established authorities. Using a qualitative netnographic method, this research gathers data from online news, social media, and YouTube. The study finds that the authority of celebrity ustazah is formed through intertwined aspects such as popularity, personal transformation, piety, and social engagement. However, methodological and scope limitations necessitate further in-depth exploration of this phenomenon.